2018
DOI: 10.2196/jmir.9190
|View full text |Cite
|
Sign up to set email alerts
|

Role of Social Media in Diabetes Management in the Middle East Region: Systematic Review

Abstract: BackgroundDiabetes is a major health care burden in the Middle East region. Social networking tools can contribute to the management of diabetes with improved educational and care outcomes using these popular tools in the region.ObjectiveThe objective of this review was to evaluate the impact of social networking interventions on the improvement of diabetes management and health outcomes in patients with diabetes in the Middle East.MethodsPeer-reviewed articles from PubMed (1990-2017) and Google Scholar (1990-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
49
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 16 publications
2
49
1
Order By: Relevance
“…The list of all potentially relevant studies that were read in full-text form but were excluded from the review can be found in Multimedia Appendix 2. Of these publications, 35 met the inclusion criteria [26-60]; of them, 32 were primary studies [26-32,34-38,40-59] and 3 were systematic reviews [33,39,60] (Figure 1). …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The list of all potentially relevant studies that were read in full-text form but were excluded from the review can be found in Multimedia Appendix 2. Of these publications, 35 met the inclusion criteria [26-60]; of them, 32 were primary studies [26-32,34-38,40-59] and 3 were systematic reviews [33,39,60] (Figure 1). …”
Section: Resultsmentioning
confidence: 99%
“…Only 1 of the 35 included studies was considered to be of high quality [31]; 19 studies were considered to be of moderate quality: the 3 systematic reviews [33,39,60,61] (Multimedia Appendix 3), all 15 randomized controlled trials (RCTs) [26-30,32,34,35,42,44,45,48,54,55,58], and 1 nonrandomized intervention [40]. The remaining 15 nonrandomized studies were weighted as being of low or very low quality, and therefore, they were removed from the narrative synthesis (these studies are listed in Multimedia Appendix 4).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations